Dissecting dynamic expression of autophagy-related genes during human fetal digestive tract development via single-cell RNA sequencing. Issue 11 (2nd November 2019) - Tan, Puwen; Ren, Yue; Zhang, Yuncong; Lin, Yunqing; Cui, Tianyu; Huang, Yan; Zhang, Yang; Ning, Lin; Yu, Jia; Gao, Shuai; Wang, Dong; Huang, He
ABSTRACT: Macroautophagy/autophagy has been demonstrated to play an essential role in embryonic development. However, the role of autophagy during human fetal digestive tract development has not been investigated. Here, by using over 5, 000 human embryonic digestive tract cells ranging from 6 weeks to 25 weeks, we explored the dynamic expression of autophagy-related genes at single-cell resolution, and found that the transcriptional activity of autophagy-related genes boosted remarkably and specifically in the early (between 6 and 9 weeks) stages. Interestingly, the small intestine cells at 9 weeks showed the most significant enrichment of autophagy-related genes than any other stages. In summary, our results for the first time revealed that autophagy may play an essential role in the development of the digestive tract, especially for the small intestine, in early human embryos. Abbreviations: GI: gastrointestinal; S-Intes: small intestine; t-SNE: t-distributed stochastic neighbor embedding